Exenatide Attenuates Non-Alcoholic Steatohepatitis by Inhibiting the Pyroptosis Signaling Pathway - Liu, Yu; Wang, Da-Wei; Wang, Dan; Duan, Bin-Hong; Kuang, Hong-Yu (Frontiers in Endocrinology, 2021)
Background/Aims: Exenatide is a glucagon-like polypeptide-1 analog, whose main clinical use is to treat type 2 diabetes. However, the mechanism of exenatide in mitigating non-alcoholic steatohepatitis (NASH) remains unclear. This study aimed to investigate the in vitro and in vivo effect of exenatide on NASH. Methods: Leptin receptor-deficient C57BL/KsJ- db/db male mice were fed with methionine-choline-deficient (MCD) diet for 4 weeks to induce NASH, while oleic acid/LPS-treated HepG2 cells were used as an in vitro cell model. Exenatide (20 µg/kg/day, subcutaneous) and specific exenatide inhibitors (20 µg/kg/day, intraperitoneal) were used to determine the effects of exenatide on NASH. Results: Exenatide treatment inhibited the pyroptosis signaling pathway to attenuate NASH. Conclusion: To the best of our knowledge, this report provides the first evidence showing that exenatide attenuated NASH by inhibiting the pyroptosis signaling pathway. Exenatide thus has important pathophysiological functions in NASH and may represent a useful new therapeutic target.